2016
DOI: 10.1007/s13187-016-1034-1
|View full text |Cite
|
Sign up to set email alerts
|

Information Needs of Hepato-Pancreato-Biliary Surgical Oncology Patients

Abstract: A marked knowledge gap exists concerning the information needs of hepato-pancreato-biliary (HPB) surgical oncology patients. We investigated the comprehensive information needs of this patient population, including the type and amount of information desired, as well as the preferred method of receiving information. A questionnaire was administered to patients being treated surgically for cancers of the liver, pancreas, gallbladder, or bile ducts at Toronto General Hospital, part of the University Health Networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…After removal of duplicates, the title and abstracts of 2986 articles were reviewed and demonstrated that patient information requirements were not the topic of focus of the publication. Comprehensive analysis of the remaining 24 articles resulted in the selection of six articles that met criteria, and are summarized in Table . Specifically these six studies examined the patient information needs in areas of cancer‐specific and treatment‐related information.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After removal of duplicates, the title and abstracts of 2986 articles were reviewed and demonstrated that patient information requirements were not the topic of focus of the publication. Comprehensive analysis of the remaining 24 articles resulted in the selection of six articles that met criteria, and are summarized in Table . Specifically these six studies examined the patient information needs in areas of cancer‐specific and treatment‐related information.…”
Section: Resultsmentioning
confidence: 99%
“…Gillespie et al . used a postal questionnaire to rank information needs of hepatobiliary cancer patients by domain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 A recent review of the information needs of hepatopancreaticobiliary (HPB) cancer patients showed that information relating to quality of life, post-operative function and life impact of surgery were nominated as the most important parts of patient preoperative experience. 3 The extent of surgical resection in PE and PD is restricted by 'non-negotiable' marginsthe pelvic side wall and retroperitoneum, respectively. Recognition of these boundaries in PE has driven the use of adjuvant therapies, both pre and intra-operatively, to enhance the surgical margin.…”
mentioning
confidence: 99%
“…High MD masks cancers, decreasing the accuracy of mammography. 3 MD is the most common method for measuring breast density. Its significance is modified by age and body mass index.…”
mentioning
confidence: 99%